2022
DOI: 10.3390/antibiotics11070892
|View full text |Cite
|
Sign up to set email alerts
|

Clinical Features and Outcomes of Monobacterial and Polybacterial Episodes of Ventilator-Associated Pneumonia Due to Multidrug-Resistant Acinetobacter baumannii

Abstract: Multidrug-resistant A. baumannii (MDRAB) VAP has high morbidity and mortality, and the rates are constantly increasing globally. Mono- and polybacterial MDRAB VAP might differ, including outcomes. We conducted a single-center, retrospective (January 2014–December 2016) study in the four ICUs (12–18–24 beds each) of a reference Lithuanian university hospital, aiming to compare the clinical features and the 30-day mortality of monobacterial and polybacterial MDRAB VAP episodes. A total of 156 MDRAB VAP episodes … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 65 publications
0
6
0
Order By: Relevance
“…Given the heterogeneity in the type and distribution of coisolates in those studies [ 9 , 11 , 12 ] and the potential interactions between S. maltophilia and certain strains [ 23 , 24 ], clearly elucidating the significance of polymicrobial infection as a prognostic factor in critically ill patients with S. maltophilia based on the current small-scale study is difficult. Conversely, a recent study on multidrug-resistant Acinetobacter baumannii VAP reported a similar result to ours, which showed a lower mortality rate in the case of polymicrobial infection than that in monomicrobial, and the attenuation of virulence due to competition with coexisting pathogens in a polymicrobial setting was suggested as a possible explanation [ 25 ].…”
Section: Discussionsupporting
confidence: 83%
“…Given the heterogeneity in the type and distribution of coisolates in those studies [ 9 , 11 , 12 ] and the potential interactions between S. maltophilia and certain strains [ 23 , 24 ], clearly elucidating the significance of polymicrobial infection as a prognostic factor in critically ill patients with S. maltophilia based on the current small-scale study is difficult. Conversely, a recent study on multidrug-resistant Acinetobacter baumannii VAP reported a similar result to ours, which showed a lower mortality rate in the case of polymicrobial infection than that in monomicrobial, and the attenuation of virulence due to competition with coexisting pathogens in a polymicrobial setting was suggested as a possible explanation [ 25 ].…”
Section: Discussionsupporting
confidence: 83%
“…During recent decades, progress in diagnostic techniques has aided in detecting the rising prevalence of polybacterial pneumonia [ 28 , 29 ]. Notwithstanding this, the studies examining the discrepancies in outcomes among patients with mono- vs. polybacterial VAP caused by the same pathogen are very limited [ 30 , 31 ]. Despite the increasing knowledge about the composition of the normal microbiome of the lower respiratory tract, previously thought to be sterile, it is still difficult to clarify the precise role of each microorganism in polybacterial lung infections: are they true etiological pathogens or merely colonizers/commensals?…”
Section: Discussionmentioning
confidence: 99%
“…It was observed that the majority of MDRAB VAP episodes were monomicrobial (67.5%), and the study concluded that monobacterial MDRAB VAP exhibited different demographic and clinical characteristics compared to polybacterial infections and was associated with worse outcomes. 94 …”
Section: Epidemiologymentioning
confidence: 99%